Environmental Risk Factors and Perinatal Outcomes in Preterm Newborns, According to Family Recurrence of Prematurity - Krupitzki, Hugo B.; Gadow, Enrique C.; Gili, Juan A.; Comas, Belén; Cosentino, Viviana R.; Saleme, César; Murray, Jeffrey C.; Camelo, Jorge S. Lopez (American Journal of Perinatology, 2013)
Objective We analyzed the role of environmental risk factors, sociodemographic characteristics, clinical characteristics, and reproductive history in preterm births and their associated perinatal outcomes in families classified according to their histories of preterm recurrence among siblings.Study Design A retrospective study was conducted at Nuestra Señora de la Merced Maternity Hospital in the city of Tucumán, Argentina. A total of 348 preterm, nonmalformed, singleton children born to multipara women were reviewed. The family history score described by Khoury was applied, and families were classified as having no, medium, or high genetic aggregation.Results Families with no familial aggregation showed a higher rate of short length of cohabitation, maternal urinary tract infections during the current pregnancy, and maternal history of miscarriage during the previous pregnancy. Families with a high level of aggregation had a significantly higher incidence of pregnancy complications, such as diabetes, hypertension, and immunologic disorders.Conclusion Reproductive histories clearly differed between the groups, suggesting both a different response to environmental challenges based on genetic susceptibility and the activation of different pathophysiological pathways to determine the duration of pregnancy in each woman.
Keywords: preterm birth; familial aggregation; pregnancy